The shariah principles of online advertising during the pandemic of COVID-19 / Nurzahidah Jaapar ... [et al.] - Jaapar, Nurzahidah; Mohamed Yusof, Mohd Faiz; Muhamad, Mohd Dani; Syed Abdullah, Sharifah Fadylawaty; Abd Halim, Anis Husna (Universiti Teknologi MARA, 2022)
The COVID-19 pandemic had a direct impact on all communities around the world. From an economic standpoint, this phenomenon can be profitable, particularly for those involved in business activities and the marketing of basic goods. However, because the country is at war with a dangerous disease, several domestic issues impede the government's efforts to protect the welfare of the people as consumers. Apart from the problem of fraudulent information on goods, numerous advertising issues occur during this pandemic due to freedom of technology usage, and trends of online advertising have caused consumers to become victims and further worsen the economic landscape in Malaysia. The evolution of technology offers powerful communications tools for society, yet restrictions on digital freedom, have raised serious concerns about the impacts on human rights and consumer protection when it comes to digital marketing. A qualitative approach is applied by emphasizing Shariah principles from the Quran alongside examples published in the mainstream press. Therefore, this article explores four cases for the study of online advertising comprised of message and information, voice and language, images and visuals, responsibility in the ads which should be based on shariah principles of truthfulness (al-Sidq), unbiased comparison (al-Adl), moderation (al-Wasatiyyah) and accountable (al-Mas'uliyyah). It is hoped that this writing will serve as a guide for all e-marketers to conduct sales activities following Shariah principles, as well as to raise consumer awareness of their rights in all situations.